2011
DOI: 10.1016/j.socscimed.2011.03.033
|View full text |Cite
|
Sign up to set email alerts
|

The intersection of school racial composition and student race/ethnicity on adolescent depressive and somatic symptoms

Abstract: Schools are one of the strongest socializing forces in the U.S. and wield considerable influence over individuals' social and economic trajectories. Our study investigates how school-level racial composition, measured by the percentage non-Hispanic white students in a school, affects depressive and somatic symptoms among a representative sample of U.S. adolescents, and whether the association differs by race/ethnicity. We analyzed Wave I data from the US National Longitudinal Study of Adolescent Health, result… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

7
61
2

Year Published

2011
2011
2022
2022

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 60 publications
(70 citation statements)
references
References 34 publications
7
61
2
Order By: Relevance
“…A few of these studies have examined the interactive effect between student race and school racial composition and have generally found that for black adolescents, attending predominantly minority schools is associated with better physical and mental health (Walsemann et al 2011) as well as a lower likelihood of engaging in some risky behaviors (Johnson and Hoffmann 2000). These findings mirror those conducted by neighborhood researchers who often find a group density effect such that health is better for residents when they live in neighborhoods where they are the numerical majority (Pickett and Wilkinson 2008).…”
Section: Introductionmentioning
confidence: 81%
See 4 more Smart Citations
“…A few of these studies have examined the interactive effect between student race and school racial composition and have generally found that for black adolescents, attending predominantly minority schools is associated with better physical and mental health (Walsemann et al 2011) as well as a lower likelihood of engaging in some risky behaviors (Johnson and Hoffmann 2000). These findings mirror those conducted by neighborhood researchers who often find a group density effect such that health is better for residents when they live in neighborhoods where they are the numerical majority (Pickett and Wilkinson 2008).…”
Section: Introductionmentioning
confidence: 81%
“…A growing body of research exists that examines the effects of school segregation and school racial composition on adolescent health and health behaviors (Johnson and Hoffmann 2000;Botticello 2009;Walsemann and Bell 2010;Walsemann et al 2011). A few of these studies have examined the interactive effect between student race and school racial composition and have generally found that for black adolescents, attending predominantly minority schools is associated with better physical and mental health (Walsemann et al 2011) as well as a lower likelihood of engaging in some risky behaviors (Johnson and Hoffmann 2000).…”
Section: Introductionmentioning
confidence: 99%
See 3 more Smart Citations